2014
DOI: 10.1002/berj.3151
|View full text |Cite
|
Sign up to set email alerts
|

Religious identity choices in English secondary schools

Abstract: This paper explores religious adolescents' reported experiences of secondary schools. Fifty‐four qualitative interviews were conducted in places of worship in three cities in England with Christians (n=46), Jews (n=38) and Muslims (n=15). Secondary schools of a religious and non‐religious character were reported as not providing a suitable environment for religious observances, nor as a place to act and behave according to participants' religious principles. Religious adolescents reported prejudice and critici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…These finding seem contrary to conclusions Berry's (1997) theory of acculturation, and encourages mental health providers to acknowledge socio-political and cultural context in models of development. Similarly, the influence of educational context on identity development of Muslim youth populations has highlighted potential institutional roles in racializing Muslim students, experiences of social exclusion, and the impact these experiences have on religious identity (e.g., Keaton, 2005;Mac an Ghaill & Haywood, 2014;Moulin, 2015;Basford, 2008). Basford (2008) described how Africanorigin Muslims in the U.S. reported perceived academic, religious, and cultural hostility, often feeling hidden and unwelcome in their schools.…”
Section: Identity and Developmentmentioning
confidence: 99%
“…These finding seem contrary to conclusions Berry's (1997) theory of acculturation, and encourages mental health providers to acknowledge socio-political and cultural context in models of development. Similarly, the influence of educational context on identity development of Muslim youth populations has highlighted potential institutional roles in racializing Muslim students, experiences of social exclusion, and the impact these experiences have on religious identity (e.g., Keaton, 2005;Mac an Ghaill & Haywood, 2014;Moulin, 2015;Basford, 2008). Basford (2008) described how Africanorigin Muslims in the U.S. reported perceived academic, religious, and cultural hostility, often feeling hidden and unwelcome in their schools.…”
Section: Identity and Developmentmentioning
confidence: 99%
“…Moulin is critical of REsilience, arguing that it has skewed the study of Islam and its representation in the RE classroom (2012,169). His own (currently small scale) emzpirical research reports Muslim students feeling further stigmatised, rather than better understood, as a result of their experiences at school (2012, 170-171;Moulin 2014). …”
Section: Re and Good Community Relationsmentioning
confidence: 99%
“…However, there are important theological and sociological factors as well as epistemological ones to be considered here. Religions typically rely on notions of authority that ensure the continuation and legitimacy of their traditions, and processes of religious identity formation have been shown to be related to processes of identification and fidelity to groups, traditions, practices and authority, rather than assent to abstract propositions (Chaudhury and Miller, 2008;Moulin, 2014;Østberg, 2000). In the case of Christianity, concepts of authority are located within a tradition with greater or lesser emphasis upon, for example, conscience, Scripture, episcopal hierarchy, or apostolic successiondepending upon the various ecclesiological positions across and within denominations.…”
Section: Issues Concerning Lack Of Authority and Religious Educationmentioning
confidence: 99%
“…Only recently has research begun to be conducted in order to understand the potential impact of Religious Education upon religious identity construction (Moulin, 2014;Streib, 2001;Thanissaro, 2012;Visser-Vogel et al, 2012). Studies with secondary school students who identified with Christianity, Islam or Judaism have found that their perspectives of Religious Education could resonate with the criticisms in the literature given above and were sometimes reported to challenge their beliefs, identifications and affiliations (Moulin, 2015, forthcoming 1 ).…”
Section: The Potential Impact Of Religious Education Upon Religious Imentioning
confidence: 99%
See 1 more Smart Citation